Effect of a nonsurgical treatment program on the gait pattern of idiopathic toe walking: a case report - Szopa A (Therapeutics and Clinical Risk Management, 2016)
Andrzej Szopa,1 Małgorzata Domagalska-Szopa,2 Weronika Gallert-Kopyto,1 Wojciech Kiebzak,3 Ryszard Plinta4 1Department of Physiotherapy, 2Department of Medical Rehabilitation, School of Health Sciences, Medical University of Silesia, Katowice, 3Faculty of Health Sciences, Jan Kochanowski University, Kielce, 4Department of Adapted Physical Activity and Sport, School of Health Sciences, Medical University of Silesia, Katowice, Poland Background: Recent studies have reported many possibilities for the treatment of idiopathic toe walking (ITW); however, none of them have been sufficiently documented. The purpose of this case study was to document the evolution of the gait pattern of a child with severe ITW using the Gillette Gait Index before and after the third and sixth weeks, a nonsurgical treatment program and then every 3 months to 1 year from the start of the treatment. This is significant because the case study shows that a nonsurgical treatment program can be an alternative treatment method for children with severe ITW.Case description: The case study involved a 5-year-old boy diagnosed with severe ITW. An orthopedist recommended a surgical treatment, but his parents refused to provide consent.Intervention: The subject participated in a 12-week nonsurgical treatment program that used tone-inhibiting casts (TICs) combined with physiotherapy based on neurodevelopmental treatment principles. The treatment protocol included the following: 1) precast preparation; 2) TICs with treatment; and 3) post-cast treatment to improve the gait pattern.Outcomes: After treatment with TICs, the range of motion of ankle dorsiflexion during stance had increased, resulting in an almost normalized gait. The patient stopped toe walking for at least 1 year.Discussion: This study demonstrates that nonsurgical treatment should be considered first, with surgical options reserved for resistant cases; however, further research is required given the current lack of knowledge about treatment outcomes using TICs and the wide use of this treatment modality in children with ITW. Keywords: tone-inhibiting casts, NDT, ROM of ankle dorsiflexion, Gillette Gait Index